Fast Retrieval Algorithm for Earth Mover's Distance Using EMD Lower Bounds and a Skipping Algorithm. (17th May 2011) - Shishibori, Masami; Koizumi, Daichi; Kita, Kenji
Abstract : The earth mover's distance (EMD) is a measure of the distance between two distributions, and it has been widely used in multimedia information retrieval systems, in particular, in content-based image retrieval systems. When the EMD is applied to image problems based on color or texture, the EMD reflects the human perceptual similarities. However, its computations are too expensive to use in large-scale databases. In order to achieve efficient computation of the EMD during query processing, we have developed "fastEMD, " a library for high-speed feature-based similarity retrievals in large databases. This paper introduces techniques that are used in the implementation of the fastEMD and performs extensive experiments to demonstrate its efficiency.